Correlation between the Capillary Blood Flow Characteristics and Endothelium Function in Healthy Volunteers and Patients Suffering from Coronary Heart Disease and Atrial Fibrillation: A Pilot Study - Petr Ermolinskiy; Yury Gurfinkel; Egor Sovetnikov; Andrei Lugovtsov; Alexander Priezzhev (Life, 2023)
Coronary heart disease (CHD) and atrial fibrillation (AF) pose significant health risks and require accurate diagnostic tools to assess the severity and progression of the diseases. Traditional diagnostic methods have limitations in providing detailed information about blood flow characteristics, particularly in the microcirculation. This study’s objective was to examine and compare the microcirculation in both healthy volunteers and patient groups with CHD and AF. Furthermore, this study aimed to identify a relationship between blood microcirculation parameters and endothelial function. Digital capillaroscopy was employed to assess the microcirculation parameters, for example, such as capillary blood flow velocity, the size of red blood cell aggregates, and the number of aggregates per min and per running mm. The results indicate significant alterations in blood flow characteristics among patients with CHD and AF compared to healthy volunteers. For example, capillary blood flow velocity is statistically significantly decreased in the case of CHD and AF compared to the healthy volunteers (p < 0.001). Additionally, the correlation between the measured parameters is different for the studied groups of patients and healthy volunteers. These findings highlight the potential of digital capillaroscopy as a non-invasive tool for evaluating blood flow abnormalities (red blood cell aggregates and decreased capillary blood flow velocity) in cardiovascular diseases, aiding in early diagnosis and disease management.